The fushi tarazu zebra element is not required for Drosophila viability or fertility. Issue 11 (26th August 2021) - Graham, Patricia L; Fischer, Matthew D; Giri, Abhigya; Pick, Leslie
Abstract: Expression of genes in precisely controlled spatiotemporal patterns is essential for embryonic development. Much of our understanding of mechanisms regulating gene expression comes from the study of cis -regulatory elements (CREs) that direct expression of reporter genes in transgenic organisms. This reporter-transgene approach identifies genomic regions sufficient to drive expression but fails to provide information about quantitative and qualitative contributions to endogenous expression, although such conclusions are often inferred. Here we evaluated the endogenous function of a classic Drosophila CRE, the fushi tarazu ( ftz ) zebra element. ftz is a pair-rule segmentation gene expressed in seven stripes during embryogenesis, necessary for formation of alternate body segments. Reporter transgenes identified the promoter-proximal zebra element as a major driver of the seven ftz stripes. We generated a precise genomic deletion of the zebra element ( ftzΔZ) to assess its role in the context of native chromatin and neighboring CREs, expecting large decreases in ftz seven-stripe expression. However, significant reduction in expression was found for only one stripe, ftz stripe 4, expressed at ∼25% of wild type levels in ftzΔZ homozygotes. Defects in corresponding regions of ftzΔZ mutants suggest this level of expression borders the threshold required to promote morphological segmentation. Further, we established true-breeding lines of homozygous ftzΔZ flies, demonstrating that the body segments missing in the mutants are not required for viability or fertility. These results highlight the different types of conclusions drawn from different experimental designs and emphasize the importance of examining transcriptional regulatory mechanisms in the context of the native genomic environment.